Uroczystości narodowe w Chyloni. (Gdynia : [s.n.], 1946)
Afisz inf. o uroczystościach 31.03.1946 wraz z programem.
Keywords: Chylonia (Gdynia, Polska ; dzielnica) -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- źródła